Levamisole in steroid-dependent nephrotic syndrome in children: A case series - Obeid Shafi; Muzamil Latief; Zhahid Hassan; Farhat Abbas; Summyia Farooq (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2022)
Nephrotic syndrome (NS) is a common clinical entity encountered in children and adults. Steriod Dependent Nephrotic Syndrome(SDNS) is one of the most common pediatric glomerular diseases. However, a significant chunk of cases follows a relapsing and remitting course. Various modalities such as cyclophosphamide, cyclosporine, tacrolimus, mycophenolate mofetil (MMF), levamisole, and rituximab have been tried in patients with steroid-dependent or frequently relapsing NS (FRNS). We describe our experience of using levamisole in nine patients with steroid-dependent NS. We used the regimen of levamisole dosing at 2.5 mg/kg on alternate days, along with alternate dosing of steroids at the lowest possible doses to achieve remission. During follow-up, two of the patients were switched over to a calcineurin inhibitor (tacrolimus). All the remaining seven patients responded to levamisole and attained remission. At 18 months follow-up, four patients were on a minimal dose of steroids (prednisolone 0.25 mg/kg alternate day) with levamisole 2.5 mg/kg, whereas three patients were on prednisolone 0.5 mg/kg/alternate day with levamisole 2.5 mg/kg alternate day. Among the patients with steroid-sensitive NS, 30%–60% are frequently relapsing or steroid-dependent forms of NS. Corticosteroids have well recognized and potentially serious adverse effects. A lot of steroid-sparing agents such as MMF, rituximab, alkylating agents like cyclophosphamide, and calcineurin inhibitors have been used in clinical medicine, to mitigate the above mentioned adverse effects of prolonged use of corticosteroids, with varying success. But these medications have significant side effects and toxicity profiles of their own. Our case series reiterates the role of levamisole in FRNS and SDNS patients without much risk of adverse events in patients and hence being a relatively less expensive treatment option.